Electrostatics and metal oxide wettability - Hanly, G.; Fornasiero, D.; Ralston, J.; Sedev, Rossen (American Chemical Society, 2011)
The wettability of a titania surface, whose surface was partially covered with a strongly based octadecyltrihydrosilane, was studied above and below the isoelectric point (or pHiep). The advancing water contact angle is at a maximum at the pHiep, decreasing symmetrically on either side in a Lippmann-like manner. The change in wettability, for a given pH, became more pronounced with increasing salt concentration. Using a non-Nernstian model of the electrical double layer, the experimental dependence of contact angle on both pH and salt concentration was satisfactorily predicted.